Síntese e caracterização de complexos de cobre, gálio e nióbio,estudos de suas citotoxicidades e interações com alvos celulares - Ivina Paula de Souza (2018)
One of the most important uses of metal compounds is in the treatment of cancer. In this work, twelve metal complexes with anticancer potential were synthesized and characterized: ten with copper(II), one with gallium(III), and a peroxocomplex of niobium(V). The copper complexes exhibit the following formula: [Cu(HL1)2] (1), [Cu2(phen)2(L1)(ClO4)2] (2), [Cu2(bpy)2(L1)(ClO4)2(H2O)2] (3), [Cu2(dmp)2(L1)(ClO4)2(H2O)2] (4), [Cu(L2)2(H2O)2] (5), [Cu(phen)(L2)](ClO4) (6), [Cu(bpy)(L2)(H2O)](ClO4) (7), [Cu(dmp)(L2)](ClO4) (8), [Cu(aap)(phen)(ClO4)2] (9) e [Cu(aap)(bpy)(ClO4)2] (10); in which H2L1 = 1,4-dihydroxyanthracene-9,10-dione; HL2 = 1-hydroxyanthracene-9,10-dione; aap = 4-aminoantipyrine; phen = 1,10-phenanthroline; bpy = 2,2-bipyridine e dmp = 2,9-dimethyl-1,10-phenanthroline. The complexes were characterized by elemental and conductivity analyses, FTIR, electronic, EPR and ESI-MS spectrometries. Slow evaporation of a solution of complex 2, in DMSOand isopropyl alcohol, yielded complex 2.1, Cu2(phen)2(L1)(dmso)2](PF6)2. The structures of complexes 2.1 and 6 were determined by single-crystal X ray diffraction. Complexes 2, 3, and 4 are dinuclear, with a bridgind L12- ligand, whereas complexes 6,7, 8, 9 and 10 are mononuclear. All copper complexes are significantly cytotoxic in myelogenous leukemia cells, K562 line, with the IC50 values of 1.0; 1.13; 10.0; 0.078; 0.945; 1.84; 12.7; 0.099; 1.8 and 26 µmol L-1 for 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10, respectively. The copper complexes interact with DNA with binding constants around 104. Interactions with DNA were also studied by spectrofluorimetry with the help of a fluorescent probe, the ethidium bromide (Eb). Complexes 2, 3, 4, 6, 7 and 8 are capableof displacing Eb from DNA base pairs. The ability of complexes 2, 3, 4, 6, 9 and 10 to oxidatively cleave plasmid DNA was investigated by agarose gel electrophoresis, in the absence and presence of reactive oxygen species (ROS) scavengers. Different ROS are generated in the DNA cleavage process and the nuclease activity follows the order 2 > 4~ 6 ~ 9 > 10 > 3. In addition, it was demonstrated that the complexes are capable of inhibiting topoisomerase-I activity. The complex [Ga2(phen)2(L1)(NO3)2(H2O)2](NO3)2. 4H2O (11) was characterized by elemental and conductivity analyses, FTIR, UV-Vis and fluorescence spectroscopies (excitation = 520 nm), ESI-MS and 1H and 13C NMR. In the FTIR spectrum of 11 the main absorptions are shifted in comparison to the free ligand spectra, evidencing the formation of a complex. In the UV-Vis spectrum, a bathocromic shift evidences the presence of the complexes in solution. The complex is fluorescent, and the fluorescence intensity is affected by the nature of the solvent. Complex 11 inhibitsthe growth of K562 cells with the IC50 = 1.0 µmol L-1 and interacts with DNA. An alternative form of cancer treatment, the photodynamic therapy (PDT), has gainedincreasing interest. The cytotoxic and photocytotoxic activities of the peroxoniobium complex, NbO2(OH)O2 - (12), was studied. The cytotoxic activity of 12 increases by 5 times upon 5 min of UV-A irradiation, with an IC50 value of 6,2 µmol L-1. The effect of12 on the activity of methylene blue, a photosensitizing agent used in PDT, was also studied. The addition of the peroxoniobate doubles the photocytotoxic effect of methylene blue. Therefore, the peroxoniobium compound prepared is a promising candidate for PDT, alone or in combination with other sensitizing agents, such as methylene blue dye.